Radiation dose in neoadjuvant chemoradiation therapy for esophageal cancer: patterns of care and outcomes from the National Cancer Data Base - Haque, Waqar; Verma, Vivek; Butler, E. Brian; Teh, Bin S. (Journal of gastrointestinal oncology, 2018)
Neoadjuvant chemoradiotherapy (CRT) for locally advanced esophageal cancer (EC) may utilize a wide variety of RT doses, without clear consensus to date. This study evaluated national practice patterns between lower dose (LD) (40-41.4 Gy) or higher dose (HD) (50-50.4 Gy) therapy, in addition to differences in survival and postoperative events. The National Cancer Data Base (NCDB) was queried [2004-2013] for patients with newly-diagnosed cT1a-T4aN0/N+M0 EC that received neoadjuvant CRT followed by esophagectomy. Multivariable logistic regression determined factors predictive of receiving LD RT. Kaplan-Meier analysis evaluated overall survival (OS), and Cox proportional hazards modeling determined variables associated with OS. Propensity score matching assessed groups in a balanced manner while reducing indication biases. Altogether, 5,025 patients met inclusion criteria; 257 (5%) received LD RT, while 4,768 (95%) received HD RT. LD RT was more likely delivered at academic centers (P=0.038), in more recent years (2009-2013, P=0.011), and to squamous cell carcinomas (P=0.001). HD RT tended to be administered with higher T stage as well as node-positive disease (P<0.05). The median OS in the LD and HD cohorts was 39.0 35.6 months (P=0.072), and 39.0 42.7 months after propensity matching (P=0.812). Dose did not independently correlate with OS on multivariate analysis (P=0.069), but treatment at academic centers correlated with improved OS (P=0.028). There were no differences between groups in the rates of 30-day readmission (P=0.182), 30-day mortality (P=0.314), or length of postoperative hospital stay (P=0.665), but the LD group experienced lower 90-day mortality (P=0.007). Although neoadjuvant LD CRT has been underutilized for EC in the United States, it is rising in more recent years. Dose did not significantly impact survival before or after propensity matching, nor did it independently predict for survival. Treatment at academic facilities independently correlated with higher survival, which has implications for patient counseling.